2006
DOI: 10.1161/01.hyp.0000215588.38536.30
|View full text |Cite
|
Sign up to set email alerts
|

New Mass Spectrometric Assay for Angiotensin-Converting Enzyme 2 Activity

Abstract: Abstract-A novel assay was developed for evaluation of mouse angiotensin-converting enzyme (ACE) 2 and recombinant human ACE2 (rACE2) activity. Using surface-enhanced laser desorption/ionization time of flight mass spectrometry (MS) with ProteinChip Array technology, ACE1 and ACE2 activity could be measured using natural peptide substrates.Plasma from C57BL/6 mice, kidney from wild-type and ACE2 knockout mice, and rACE2 were used for assay validation. Plasma or tissue extracts were incubated with angiotensin I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 41 publications
(80 reference statements)
6
75
0
Order By: Relevance
“…Although our studies find that ACE2 inhibition augmented the levels of ANG II in the proximal tubules, other enzymes including neprilysin likely influence the peptide's metabolism. These data on the contribution of ACE2 are consistent with recent studies by Elased et al (11) and our group that demonstrated ACE2-dependent conversion of ANG II to ANG-(1-7) in membrane fractions of mouse kidney and rat renal cortex (13), respectively. However, the characterization of ANG II metabolism in the proximal tubules of sheep markedly differs from that reported by Burns and colleagues (23) in the rat kidney.…”
Section: Discussionsupporting
confidence: 92%
“…Although our studies find that ACE2 inhibition augmented the levels of ANG II in the proximal tubules, other enzymes including neprilysin likely influence the peptide's metabolism. These data on the contribution of ACE2 are consistent with recent studies by Elased et al (11) and our group that demonstrated ACE2-dependent conversion of ANG II to ANG-(1-7) in membrane fractions of mouse kidney and rat renal cortex (13), respectively. However, the characterization of ANG II metabolism in the proximal tubules of sheep markedly differs from that reported by Burns and colleagues (23) in the rat kidney.…”
Section: Discussionsupporting
confidence: 92%
“…That similar hemodynamic patterns were observed in diabetic ACE2 KO mice and wild-type mice receiving a selective ACE2 inhibitor suggests that circulating ACE2 may have an important role in the induction and maintenance of diabetic hyperperfusion. Although previous studies have failed to detect ACE2 activity in human plasma samples (26), the increased sensitivity of our assay and the ninefold higher ACE2 activity in murine samples compared with human plasma may partly explain this discrepancy. Moreover, the angiotensinase activity observed in this study was consistent with that of systemic ACE2, as it was inhibited by the same inhibitors (MLN-4760, EDTA, and Ang II; data not shown), and this enzyme activity was absent in ACE2 KO mice.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast to ACE, circulating ACE2 is low to nondetectable in rodents and humans, and tissue sources of the enzyme are more likely to influence the local RAS (12,40). Diabetic renal injury is generally associated with a reduction in the activity and/or expression of renal tissue ACE2, which may contribute to a deleterious imbalance in the relative expression of ANG II to Ang-(1-7) (21,26,39,52,53,60,63).…”
mentioning
confidence: 99%